2019
DOI: 10.3390/su11133655
|View full text |Cite
|
Sign up to set email alerts
|

In-Plant Logistics Simulation Model for the Catering Service Industry Towards Sustainable Development: A Case Study

Abstract: An increasing number of people are conscious of the environmental awareness in various industries, particularly in city areas. It is now a popular trend for the urban catering service industry to outsource its labor-intensive activities, such as dishwashing, to a central dishwashing facility, in which labor force management and optimization are essential. Moreover, the increasing labor cost and fluctuating labor supply drive the increasing need for labor force optimization. This research develops an in-plant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…This input is a crucial issue concerning the development of simulation models which correspond to actual conditions in real-life logistics facilities. Without such actual conditions, especially in the case of hypothetical systems, an analysis of the sensitivity of system parameters would not be valid (it should be noted that the model has not been validated since it is a model of the hypothetical warehouse, however it was verified [ 32 ]; in contrast to other research papers e.g., [ 113 ], the workers and equipment are not assumed to work in modeled warehouse in a constant manner, which is due to the application of the PRNG; therefore the simulation model may be more adequate for reflecting real-life situations and, at the same time, more relevant to actual working conditions). The original PRNG was used to generate picking lists with randomly selected numbers of rows and quantities of items to pick.…”
Section: Discussionmentioning
confidence: 99%
“…This input is a crucial issue concerning the development of simulation models which correspond to actual conditions in real-life logistics facilities. Without such actual conditions, especially in the case of hypothetical systems, an analysis of the sensitivity of system parameters would not be valid (it should be noted that the model has not been validated since it is a model of the hypothetical warehouse, however it was verified [ 32 ]; in contrast to other research papers e.g., [ 113 ], the workers and equipment are not assumed to work in modeled warehouse in a constant manner, which is due to the application of the PRNG; therefore the simulation model may be more adequate for reflecting real-life situations and, at the same time, more relevant to actual working conditions). The original PRNG was used to generate picking lists with randomly selected numbers of rows and quantities of items to pick.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the article (Terelak Jardzioch & Biniek, 2018), the impact of the use of production scheduling on energy efficiency was analysed, and the results showed that in the scheduling of production orders, from 5 to 45% electricity savings can be achieved, while in my research, I am going to use the scheduling of production orders and check whether it will affect the sustainable development of the company. In the article (Lee, Zhang & Ng, 2019), the authors presented a comparison of simulation results with a real process, how decisions are made to optimise the workforce, improve performance in a specific dishwasher factory, and the impact of these studies on sustainable development. Optimisation of work on the production line is presented.…”
Section: Application Of Simulation Researchmentioning
confidence: 99%
“…With regard to flight time and fuel consumption, the staple segment was cruise [47][48][49]. The optimal flight trajectories in the cruise stage are determined based on fuel consumption, flight time, CO 2 emission and contrail formation [50][51][52]. However, as the amount of CO 2 emission is proportional to fuel consumption [7,53,54], this paper only considers fuel consumption as a factor instead of CO 2 .…”
Section: Figurementioning
confidence: 99%